Self esteem, life satisfaction, stressfull life event as correlates of inner meaning fulfilment among students University of Ibadan (2003)
The study investigated the interrelationships between psychological variables such as Stressful life event, Self-esteem, Life satisfaction and Inner meaning fulfilment (IMF) among students of the University of Ibadan. There were eight hundred and eight five (885) participants with 449 (50.7%) males and 436 (49.3%) females. The mean age for the participants was 26.2 years with a standard deviation of 6.0 and age range from 15 - 60 years. The IMF scale (Logo test), which is in form of a questionnaire, was used for the data collection. Inter - correlation of the variables was conducted using the Pearson product correlation to test the three predictor variables which were significantly related to inner meaning fulfilment except the life satisfaction, (r = .06) was not significant. Self-esteem had a positive significant correlation with IMF (r = .18) although a negative relationship was expected while in life stressful event (r - 13) a negative correlation was found with IMF scale. Based on these findings a further research with those predictor variables with inner meaning fulfilment needs to be conducted in order to verify those issues raised in this study.